2021
DOI: 10.1002/pc.26028
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale simulation and theoretical prediction for the elastic properties of unidirectional fiber‐reinforced polymer containing random void defects

Abstract: Polymer‐matrix composites are widely used in various industries due to their high specific strength and specific stiffness. However, the void formation is inevitable as a by‐product during manufacturing processes, which may have negative effects on its mechanical properties. The purposes of this paper are to quantitatively evaluate the influence of voids on the anisotropic elastic properties of composites and to provide corresponding theoretical prediction models. Firstly, three‐dimensional representative volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
3
4
0
Order By: Relevance
“…Moreover, the burn‐off method yielded more consistent V f results for all laminate types, and also in general greater consistency with the measured material densities (i.e., higher V f corresponded to higher material densities). The average void content of unconditioned [0°] 16 laminates was 2.84%; this level is consistent with values obtained by Chu et al [ 62 ] and the trend found by Mujahid et al [ 63 ] for high V f laminates. The average thickness of conditioned in‐plane shear specimens was slightly lower than unconditioned specimens.…”
Section: Resultssupporting
confidence: 90%
“…Moreover, the burn‐off method yielded more consistent V f results for all laminate types, and also in general greater consistency with the measured material densities (i.e., higher V f corresponded to higher material densities). The average void content of unconditioned [0°] 16 laminates was 2.84%; this level is consistent with values obtained by Chu et al [ 62 ] and the trend found by Mujahid et al [ 63 ] for high V f laminates. The average thickness of conditioned in‐plane shear specimens was slightly lower than unconditioned specimens.…”
Section: Resultssupporting
confidence: 90%
“…The present model depicts a similar detrimental effect of pores on the transversal stiffness and strength as similarly predicted in literature works with geometrical models of the pores for carbon composites. [7][8][9] In particular, Chu and Jiang numerically predicted a drop of the transverse modulus of about 10% at a void content of 4%, which correlates well with the present numerical results. 8,47 He 7 and Liu 12 predicted a strength drop between 15% and 25% at the same void content, which agrees well with the observed 15% drop in this work.…”
Section: Numerical Resultssupporting
confidence: 89%
“…79 In particular, Chu and Jiang numerically predicted a drop of the transverse modulus of about 10% at a void content of 4%, which correlates well with the present numerical results. 8,47 He 7 and Liu 12 predicted a strength drop between 15% and 25% at the same void content, which agrees well with the observed 15% drop in this work. With about 90,000 tetrahedron elements compared to the 600,000 used by Chu in Ref.…”
Section: Evaluation Of Materials Scatter In Composite Unit Cellssupporting
confidence: 90%
See 1 more Smart Citation
“…Nevertheless, design of composites plates involves several variables since it is a multiscale task [17,18] and experimental results usually have a quite limited application. [19] On the one hand, analytical investigations have the advantage of good approximations and attractive formulae for optimization procedures.…”
Section: Introductionmentioning
confidence: 99%